Student Engagement of Learning Science In Augmented Reality (AR) - Muhammed, Muhammad Habib (IRC, 2019)
Learning environment in secondary schools is causing the students to become less motivated to learn in their study. This is due to the fact of less immersive and interactive learning throughout the class period. In order to overcome this situation, an interactive approach is taken where the learning and school exercises are done via Mobile Augmented Reality based on the syllabus given. The Augmented Reality consists of 3D Model included with interactive graphics, sounds and exercises for students.